Pengaturan dan Kedudukan Debitur Wanprestasi dalam Proses Eksekusi Penjualan Objek Hak Tanggungan Milik Pihak Ketiga Secara di Bawah Tangan - Kasiani, Kasiani; Susetiyo, Weppy (Jurnal Supremasi, 2024)
Credit agreements utilizing Mortgage Rights provide preferential treatment to creditors. In case of debtor default, creditors can liquidate the mortgaged land to settle the debt. The Indonesian Mortgage Law (UUHT) only allows for extrajudicial foreclosure with consent from the grantor and the mortgagee. However, the regulation concerning third-party foreclosure and the debtor's position in this process under UUHT remains ambiguous. This research employs a normative approach, utilizing statutory and conceptual methods. Findings reveal that UUHT does not specifically regulate third-party foreclosure sales. Debtors act solely as recipients of debt repayment rights, yet they hold influence in determining the foreclosure process. Consequently, creditors lose the ability to independently sell the property and recover payments, thus diminishing creditor preference.